Accelerated rates of large-scale mutations in the presence of copper and nickel - Chain, Frédéric J.J.; Flynn, Jullien M.; Bull, James K.; Cristescu, Melania E. (Genome Research, 2019)
Mutation rate variation has been under intense investigation for decades. Despite these efforts, little is known about the extent to which environmental stressors accelerate mutation rates and influence the genetic load of populations. Moreover, most studies on stressors have focused on unicellular organisms and point mutations rather than large-scale deletions and duplications (copy number variations [CNVs]). We estimated mutation rates in Daphnia pulex exposed to low levels of environmental stressors as well as the effect of selection on de novo mutations. We conducted a mutation accumulation (MA) experiment in which selection was minimized, coupled with an experiment in which a population was propagated under competitive conditions in a benign environment. After an average of 103 generations of MA propagation, we sequenced 60 genomes and found significantly accelerated rates of deletions and duplications in MA lines exposed to ecologically relevant concentrations of metals. Whereas control lines had gene deletion and duplication rates comparable to other multicellular eukaryotes (1.8 × 10−6 per gene per generation), the presence of nickel and copper increased these rates fourfold. The realized mutation rate under selection was reduced to 0.4× that of control MA lines, providing evidence that CNVs contribute to mutational load. Our CNV breakpoint analysis revealed that nonhomologous recombination associated with regions of DNA fragility is the primary source of CNVs, plausibly linking metal-induced DNA strand breaks with higher CNV rates. Our findings suggest that environmental stress, in particular multiple stressors, can have profound effects on large-scale mutation rates and mutational load of multicellular organisms.
10.1101/gr.234724.118